Application of Particle Swarm Optimization and Ant Colony Optimization integration in the Aerator Reducer Optimization Design - Wu Dongmin; Rui Yannian; Shen Ming (Jixie chuandong)
The Ant colony algorithm has the defects of premature convergence as its parameter selection greatly dependent on the personal experience.In order to solve the problem,a PAAA algorithm to optimization design the planetary gear reducer of the aerator is presented.To meet the constraints condition of structure and strength,taking the minimum volume and the highest efficiency of the planetary gear train as objective functions,its optimization mathematics model is established.The Matlab program is wrote to solve the mathematical model by using PAAA algorithm.The research results show that planetary gear train has smaller volume and higher efficiency under assuring the design requirements.The results also verified the PAAA optimization has the advantage of effective,accurate and reliable.